Case of Lumbar Spondylolisthesis - Borkar, Ashok (Homœopathic Links, 2013)
This is a case of a 33-year-old male suffering from lumbar Spondylolisthesis for three years. He was in severe pain and had tried different therapies. He had been advised to undergo surgery but after homeopathic treatment had no need for surgery.
Keywords: Lumbar spondylolisthesis; Aranea diadema